Les Particules Élémentaires: An Exercise in Optimism - Víquez Jiménez, Alí (2016)
This essay performs a reading exercise of the novel Les particules élémentaires, by Michel Houellebecq (1998). It seeks to specify the socio-historical, scientific, and philosophical basis on which the novel is rooted.